Spiders of the market : Ghanian trickster performance in a web of neoliberalism - Donkor, David Afriyie (African expressive cultures., 2016)
The Ghanaian trickster-spider, Ananse, is a deceptive figure full of comic delight who blurs the lines of class, politics, and morality. David Afriyie Donkor identifies social performance as a way to understand trickster behavior within the shifting process of political legitimization in Ghana, revealing stories that exploit the social ideologies of economic neoliberalism and political democratization. At the level of policy, neither ideology was completely successful, but Donkor shows how the Ghanaian government was crafty in selling the ideas to the people, adapting trickster-rooted performance techniques to reinterpret citizenship and the common good. Trickster performers rebelled against this takeover of their art and sought new ways to out trick the tricksters.